The Fracture Toughness of Heat Cured Acrylic- Natural Rubber/Silicone Rubber Blend Reinforced with Pomegranate Peels Powder (Journal of University of Babylon for Engineering Sciences, 2019)
The development of PMMA resin in denture base fabrication by using the strengthen method represent important factor in the last years, so this study aims to development the mechanical strengthens of PMMA denture base by manufacturing samples based on two types of polymers blends are (poly methyl methacrylate (PMMA) resin: 2% (silicone rubber (SR)) and (PMMA resin:  2% natural rubber (NR)),  each one of them used as a matrix material,  reinforced by natural nanoparticles of pomegranate peel (PPP), with selected weight fractions ratios (0.0, 0.1, 0.3, 0.5 & 0.7% wt.). Some mechanical properties and analytical of (FTIR) were investigated. The results showed an appreciably improvement in the values of flexural strength, max. Shear stress, impact strength and fracture toughness for both groups of hybrids nanocomposites specimens comparing with matrix materials of (PMMA: 2%SR) and (PMMA: 2%NR). Hybrid nanocomposites specimens that based on polymer blend (PMMA: 2%NR) as matrix material  reinforced with PPP nanoparticle ,  showed the highest values in these properties  (144MPa, 12MPa, 10KJ/m² and 5.74MPa.m½) respectively, as compared with specimens of hybrid nanocomposites  (PMMA: 2%SR): X% PPP) . On the basis of these results, it can be conclusion that the addition of 2% natural rubber with pomegranate peels powder nanoparticles to the poly methyl methacrylate material is one of the hopeful materials in use to improve the fracture strength for the complete or partial dentures base.